Synbiotic, probiotic and neem leaf as alternatives to antibiotic growth promoter in broiler diet (Bangladesh Journal of Animal Science, 2022)
The feeding trial was carried out to compare the effect of probiotic, synbiotic and neem (Azadirachta indica) leaf as alternatives to antibiotic in broiler chicken diets. The experiment was performed for a period of 28 days with a number of 500 day-old straight run broiler chicks. Birds were divided into five dietary treatment groups with 4 replications having 25 birds in each. The dietary groups were; control (Basal diet), synbiotic, probiotic, neem leaf powder (NLP) and antibiotic group. The experimental diets were consisted as broiler starter (day-old to 14 days) and broiler grower (15 to 28 days). The supplementation of synbiotic, probiotic, NLP and antibiotic in the broiler diets had significant effect on growth performance. Diets supplemented with synbiotic showed significantly (p